Accountability in the post Malaysian code on corporate governance: the role of audit committee/independent directors - Muhamad Sori, Zulkarnain; Abdul Hamid, Mohamad Ali; Mohd Nasir, Azhar; Yusoff, Azemin; Hashim, Narimah; Mohd Said, Ridzwana; Mat Daud, Zaidi (EuroJournals, 2008)
Audit committee has been in existence for many decades. The establishment of audit committee aimed to mitigate corporate fraudulent or creative accounting practices through internal control initiated by independent and effectively functioning non-executive members of audit committee. An effectively functioning audit committee helps to improve corporate governance practice of firms. This study identifies the attributes of an effective audit committee from audit committee chairman's perspective. The study utilized questionnaire survey approach, where a total of 200 questionnaires were distributed to chairman of audit committee of companies that listed on the Main and Second Board of the Kuala Lumpur Stock Exchange. Seventy-two useable questionnaires were returned (or 36% response rate). Using factor analysis; the respondents rated highly the effectiveness attributes, which explained 72% of the variance in all of the variables. Three factors were extracted: overall features (54% variance), model to others (10% variance) and review and analysis of standards (8% variance). In general, the respondents believed that an effective audit committee should have the following attributes: sophisticated accounting knowledge, review of financial statements, traditional role in accounting and auditing to ensure auditor independence and good management, and internal control.